Kinodynamic planning for a fixed-wing aircraft in dynamic, cluttered environments : a local planning method using implicitly-defined motion primitives - Cowley, Edwe Gerrit (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)--Stellenbosch University, 2013.